Pengaruh Kompetensi Kepribadian Guru Akidah Akhlak Terhadap Perilaku Peserta Didik - Raito, Raito; Azhari, Hilma Hudaifah (STAI Al-Musaddadiyah Garut, 2025)
The personality competence of the teacher of moral beliefs affects the formation of student behavior, this condition is because learning not only produces changes in knowledge but also brings changes in students' attitudes or behaviors. Teachers as one of the spearheads in shaping students' behavior and morals have an important role, because the figure of the teacher in the child's view will be a benchmark for students' attitudes, both in the classroom and outside the classroom. In addition, researchers' attention to Islamic Religious Education has recently had problems related to the low character of students in schools which has become a sharp focus of the community. Seeing these problems, the purpose of this research is to describe the process of influencing the personality competence of moral faith teachers on student behavior. The subjects in this study are grade VIII students of MTs Al-Musaddadiyah Garut, which is 20 students. As for the results of the study, Fcal > Ftabel is 101.142 > 4.38, then the decision taken is H0 is rejected, then Ha is accepted. Based on the calculation of the determination coefficient, it shows that there is an influence of the personality competence of the moral faith teacher on student behavior by 77.5% and the remaining 22.5% is influenced by other factors that are not included in this study. Keywords: Personality Competence, Learner Behavior.